The Main Character in the Novel Cover of Night by Linda Howard: Psychological Analysis - Saud, Indah Wardaty; Jusuf, Harni; Bin Tahir, Saidna Zulfiqar (Language Development Center, 2022)
Background: Novels are book-length fictional prose narratives, usually representing characters and actions with some degree of realism. Because of the main character in Linda Howard’s Novel Cover Night, it is important to study Purpose: to find out and describe the psychology of the main character in the novel Cover of Night by Linda Howard so that it helps obtain information and knowledge about the linguistic psychology of the main character, as well as developing literature. Studies related to character building. Method: This study uses the library method. The researcher will describe the main character of the novel. Namely Linda Howard’s novel “Cover of Night” as the primary data source. The other is about the characters in the novel. Researchers use a psychological approach to analyze the novel. Results and Discussion: The results of this study are that the main characters, Cate Nightingale and Calvin Harris, in this novel are portrayed positively as good characters, while Cate Nightingale is a loyal woman. She had no relationship with other men after her husband’s death. Her love for her husband made her blind and never attracted to other men. Cate is also a hardworking woman. He has to work hard to earn money to raise his children, so Calvin falls in love with Cate. Calvin Harris is a strong and mighty man with such a significant character that he makes an impression on one’s life. Conclusions and Implications: This research provides positive inspiration about Calvin’s personality as a character who has a heroic nature. This novel helps obtain information about the linguistic psychology of the main character, who is always brave in protecting someone he loves, even though he has to risk his life.